Transcription factors STAT-4, STAT-6 and CREB regulate Th1/Th2 response in leprosy patients: effect of M. leprae antigens - Upadhyay, Rajni; Dua, Bhavyata; Sharma, Bhawna; Natrajan, Mohan; Jain, Ajai Kumar; Kithiganahalli Narayanaswamy, Balaji; Joshi, Beenu (BMC infectious diseases, 2019)
Leprosy is an ideal human disease to study T cell regulation as patients show correlation between cytokine skewed Th1-Th2 responses and clinical forms of the disease. The Role of transcription factors on the modulation of Th1 and Th2 responses by M. leprae antigens has not been adequately studied. In the present study, we studied the effect of M. leprae antigens on transcription factors STAT-4, STAT-6 and CREB and their correlation with Th1/Th2 cell mediated immune responses in leprosy. Leprosy patients of both categories of tuberculoid leprosy (BT/TT) and lepromatous leprosy (BL/LL) were selected from the OPD of NJ1L & OMD, (ICMR), Agra and healthy individuals (H) were chosen from the staff and students working in the institute. Peripheral blood mononuclear cells (PBMCs) of the study subjects were stimulated with M. leprae antigens (WCL, MLSA, and PGL-1). Sandwich ELISA was done in the culture supernatants of healthy and leprosy patients to detect IL-4, IL-10 and IFN-γ. Further, expression of IFN-γ and IL-4 and activation of STAT4, STAT6 and CREB transcription factors in CD4 T cell with or without stimulation of M. leprae antigens was investigated by flow cytometry. Lepromatous leprosy patients showed significantly lower IFN-γ and higher IL-4 levels in culture supernatant and significantly low expression of IFN-γ and higher expression of IL-4 by CD4 T cells than healthy individuals with or without antigenic stimulation. Antigenic stimulation significantly increased IL-10 in BL/LL patients but not in BT/TT patients or healthy individuals. PGL-1 stimulation led to significantly higher activation of STAT-6 in BT/TT and BL/LL patients in comparison to healthy individuals. All the three antigens led to activation of CREB in healthy and BT/TT patients but not in BL/LL patients. Our findings show that M. leprae antigens differentially modulate activation of T cell transcription factors STAT-4/STAT-6 and CREB. These transcription factors are well known to regulate Th1 and Th2 mediated immune response which in turn could play vital role in the clinical manifestations of leprosy. These observations may help to determine how these T cell transcription factors affect the development of immune dysfunction and whether these new pathways have a role in immunomodulation in intracellular diseases like leprosy and TB.